Re-Assessment Teknologi Pemurnian Air Laut Reverse Osmosis Di Pulau Hiri - Sandi Rais (Department of Electrical Engineering, University of Patria Artha, 2022)
This research aims to review the sea water purification technology, which no longer functions as a source of clean water for the people of Hiri Island. Identifying clean water problems and the need for clean water for the people on Hiri Island was analyzing the constraints and costs of implementing which re-operate the reverse osmosis technology located on Hiri Island for development. The results of the calculation of water consumption for the total head of the family in Hiri Island is 829 x 144 liters/day = 119,376 m3/day. By re-activating the reverse osmosis technology already available on Hiri Island, the water needs of all residents can be met. The obstacle experienced by the sea water purification technology that was built in Togolobe Village, according to the manager who runs the sea water purification technology, is that the filter equipment is damaged. According to the manager, the damaged equipment has been looked for in Ternate to be replaced. However, the filter is not available in Ternate or North Maluku. The manager has had time to build coordination in the procurement of replacement filter equipment. However, there is no certainty that the technology can no longer be used until now. To develop the operation of reverse osmosis technology required cost is Rp. 11,532,000.